History of the Ottoman Empire and modern Turkey - Shaw, Stanford J. (Cambridge University Press, 1976)
Analyzes developments in the rise of the Ottoman Empire, from 1280 to 1808, and its modernization and demise in the nineteenth and early twentieth centuries.